UPAYA YANG DILAKUKAN PADA MASYARAKAT PESISIR MENGENAI EKSPLOITASI MASYARAKAT DI DESA BIANGKEKE KECAMATAN PA’JUKUKANG KABUPATEN BANTAENG - Hasbiah, Hasbiah; AS, Husain.; Sulolipu, Andi Annisa (Jurnal Ilmiah Global Education, 2023)
This research aims: 1). To find out and explain the efforts of coastal communities, especially fishermen, regarding community exploitation of coastal resources in Biangkeke Village, Pa'jukukang District, Bantaeng Regency. This research will be carried out in Biangkeke Village, Pa'jukukang District, Bantaeng Regency. This research basically describes and analyzes phenomena. social activity events, attitudes, beliefs, perceptions, thoughts of people individually and in groups. The development of coastal community institutions based on local resources will increase community participation in decision making and monitoring of resource potential management. Thus it will better guarantee the continuity of increasing income and preserving its resources. The method used is descriptive with a qualitative approach, which has natural characteristics (natural setting) as a direct, descriptive data source. The focus of the research is fishermen. This research basically describes and analyzes phenomena. social activity events, attitudes, beliefs, perceptions, thoughts of people individually and in groups. Solving problems that exist in research requires in-depth, regular and continuous investigation, in order to find out how the research steps should be. This is very important in the research process that is carried out in a planned and systematic manner. The results of this study indicate that 1). Counseling was held related to coastal areas, location utilization and land conversion in coastal areas right on the shoreline from residential areas to access for fishing boats to obtain natural resource products. 2.) Form farmer groups to empower coastal areas to plant seaweed seeds. 3.) Empowerment as a process of developing, becoming self-sufficient, self-help, strengthening the bargaining position of the grassroots community against pressure forces in all fields and sectors of life. An independent society as a participant means an open space and capacity to develop creative potential, control the environment and its own resources, solve problems independently, and participate in determining the political process in the realm of the state. The community participates in the process of development and governance.